2016
DOI: 10.1002/clc.22531
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Association Between Regular Physical Activity and Incident Atrial Fibrillation: A Meta‐analysis of 13 Prospective Studies

Abstract: Several studies investigated the role of physical activity in atrial fibrillation (AF), but the results remain controversial. We aimed to estimate the association between physical activity and incident AF, as well as to determine whether a sex difference existed. We systematically retrieved relevant studies from Cochrane Library, PubMed, and ScienceDirect through December 1, 2015. Data were abstracted from eligible studies and effect estimates pooled using a random-effects model. Thirteen prospective studies f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 38 publications
2
21
1
Order By: Relevance
“…Long‐term vigorous physical training is associated with an increased risk of AF in athletes, but this association does not exist in nonathletes . Interestingly, there is a sex difference in the aforementioned association; in brief, an increased level of physical activity is most likely associated with an increased risk of AF in men and a reduction of AF incidence in women . These inconsistent results may be due to the imprecision of physical activity assessment via self‐reported rather than direct measurement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long‐term vigorous physical training is associated with an increased risk of AF in athletes, but this association does not exist in nonathletes . Interestingly, there is a sex difference in the aforementioned association; in brief, an increased level of physical activity is most likely associated with an increased risk of AF in men and a reduction of AF incidence in women . These inconsistent results may be due to the imprecision of physical activity assessment via self‐reported rather than direct measurement.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Interestingly, there is a sex difference in the aforementioned association; in brief, an increased level of physical activity is most likely associated with an increased risk of AF in men and a reduction of AF incidence in women. 26 These inconsistent results may be due to the imprecision of physical activity assessment via self-reported rather than direct measurement. Although physical-activity habits are considered the main determinant of physical fitness, 27 we should not equate physical fitness with habitual physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…In women, moderate exercise has been reported to be associated with a reduced risk of AF. 18 A recent meta-analysis reported that moderate-intensity exercise was associated with a 9% and 19% risk reduction of AF in women and men, respectively, in comparison with sedentary individuals. 19 Men who performed intense exercise had a 3-fold increased risk of AF in comparison with sedentary individuals, whereas women performing vigorous exercise had a 28% reduction in incident AF.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Overall, there is inadequate evidence to reliably affirm a proarrhythmogenic effect for exercise in women. 43 It is likely that sex physiological differences, attenuated exercise-induced cardiac remodelling, or a lower exercise intensity in women than in men could also contribute to the lack of an evident exercise-induced increased risk of AF. 44 The risk of AF conferred by exercise progressively increases with the intensity of exercise ( Figure 2B).…”
Section: [H2] Exercise-induced Afmentioning
confidence: 99%